Growth of a wasteland - Bhaduri, Amit (2008)
The paper begins by drawing some analogies between China and India to emphasise the link between growing inequality and acceleration in the rate of economic growth in both countries despite the differences in their political systems. it then argues how inequality feeds on growth and growth feeds on inequality through a mechanism of mutual positive feedback of cumulative causation in which land acquisition by the government for `public purpose' to help corporate-led industrialisation plays an increasingly prominent role. The paper ends by pointing out the problems it raises for Indian democracy. - Reproduced.
Keywords: Economic growth - India; Economic growth